Activity Based Costing (ABC) System on the Calculation of Cost of Goods Sold (COGS) - Ridwan Ridwan; Shirley Mo Ching Yeung; Andri Catur Trissetianto (Greenation International Journal of Economics and Accounting, 2023)
This study investigates the application of Activity Based Costing (ABC) in the calculation of Cost of Goods Sold (COGS) and its impact on cost management and business performance. The research aims to explore how the implementation of ABC can improve the accuracy of COGS, enhance cost efficiency, and increase profitability within various industries, including manufacturing, retail, and services. Data were collected through surveys and interviews from 30 companies in Indonesia that have adopted ABC in their cost accounting systems. The results of paired sample t-tests indicated a significant improvement in COGS accuracy, with an average increase of 20% after ABC implementation. Furthermore, the study found that ABC positively impacted cost efficiency (83.33%), profitability (66.67%), and decision-making efficiency (73.33%). The research also identified the challenges of ABC adoption, including the high initial investment and complexity, particularly for small and medium-sized enterprises (SMEs). The findings highlight the long-term benefits of ABC in improving cost allocation, optimizing resource use, and enhancing strategic decision-making. This study contributes to the growing body of literature on cost management and provides practical insights for businesses considering ABC adoption.